Fertilizer Induced Amelioration of Nitrogen Fixation under Moisture Stress in Chickpea - Kumar, Rajiv; Kuhad, M S (Annals of Arid Zone, 2016)
The investigations were carried out on chickpea (Cieer arietinum L.) cultivar HC-I under pot culture with the objective to ameliorate the deleterious effects I of water stress using phosphorus and potassium alone and in combinations at vegetative and reproductive stages. At both the stages, water stress-induced decline in relative water content (50-60%) decreased the nitrogen fixation in terms of ARA (40-47%) and nodule leghaemoglobin content (30-40%). Fertilizer applications considerably improved the RWC of leaf (upto 7%), N2-ase activity (3-14%) and leghaemoglobin content of nodule (10-25%) under moisture deficit conditions. Phosphatic fertilizers proved better than potassium in ameliorating deleterious effects of water stress on nitrogen fixation. Moreover, their interaction effects were still better.